Kaedah pembangunan semula kawasan Brownfield kajian kes : Connaught Avenue - Lew, Kin Yoon (2010)
Brownfield redevelopment is a relatively new idea of redevelopment in our country. The main factor Brownfield development is a priority for Brownfield development is a solution to the problem of shortage of land in the city center. Brownfield redevelopment will also create many job opportunities to the unemployed. The main factor Brownfield redevelopment should be encouraged because of the development will reduce the explore of the new forest because there are still Brownfield sites can be developed. There are three key actor in the development of Brownfield sites, they consist of property developers, Local Authorities and the purchaser. Brownfield redevelopment more popular now is because there is high demand for land in major cities such as Kuala Lumpur. The developer is not interested in developing Brownfield sites because they often faced with the problem of uncertainty in the implementation of the redevelopment of this area. In this research , there was a special government agency should be established to manage the development of potential Brownfield. Another important point in the research of the redevelopment of Brownfield sites are special guide lines should be established for the reference of all parties involved. To achieve the objectives of this study, researchers used data on primary and secondary data to make a referral-based, primary obtained through interviews with those involved in the development and use of a questionnaire to those who are directly involved in the development of Brownfield sites. The researcher found that the redevelopment of Brownfield sites have many advantages which should be promoted. The proposed research is a comprehensive guideline for the management of all party involved should be established. If there is a government agency that can assist in this development and there are comprehensive guidelines, the interests of developers and government departments to develop Brownfield sites will increase. Brownfield areas are areas that need to be developed for these the benefits to all segments of society.